AP3B1 Has Type I Interferon-Independent Antiviral Function against SARS-CoV-2 - Subramanian, Gayatri; Hage, Adam; Feldmann, Friederike; Chiramel, Abhilash I.; McNally, Kristin L.; Sturdevant, Gail L.; Beare, Paul A.; Best, Sonja M. (Viruses, 2024)
The unprecedented research effort associated with the emergence of severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) included several extensive proteomic studies that identified host proteins that interact with individual viral gene products. However, in most cases, the consequences of those virus–host interactions for virus replication were not experimentally pursued, which is a necessary step in determining whether the interactions represent pro- or anti-viral events. One putative interaction commonly identified in multiple studies was between the host adaptor protein complex 3 (AP-3) subunit B1 (AP3B1) and the SARS-CoV-2 envelope protein (E). AP3B1 is one subunit of AP-3 required for the biogenesis of lysosomal-related organelles (LROs), and its function impacts important disease processes including inflammation and vascular health. Thus, interactions between AP3B1 and SARS-CoV-2 might influence the clinical outcomes of infection. To determine if AP3B1 has a role in the SARS-CoV-2 replication cycle, we first confirmed the interaction in virus-infected cells using immunoprecipitation (IP) and immunofluorescence assays (IFA). AP3B1 is required by multiple viruses to aid in the replication cycle and therefore may be a therapeutic target. However, we found that the overexpression of AP3B1 suppressed SARS-CoV-2 replication, whereas the siRNA-mediated depletion of AP3B1 increased the release of infectious virus, suggesting an antiviral role for AP3B1. Together, our findings suggest that AP3B1 is an intrinsic barrier to SARS-CoV-2 replication through interactions with the viral E protein. Our work justifies further investigations of LRO trafficking in SARS-CoV-2 target cells and their role in viral pathogenesis.